466PCancer immunotherapy efficacy and patients' age: A systematic review and meta-analysis. (24th November 2019) - Jiang, Y; Su, Z
Abstract: Background: Checkpoint inhibitors have been regarded as an alternative to docetaxel as the new standard second-line therapy or even first-line therapy in advanced non-small cell lung carcinoma (NSCLC), nevertheless, little is known about the effect of patients' age on the efficiency of immune checkpoint inhibitors as cancer treatments. Thus, we did a systematic review and meta-analysis to assess the immune checkpoint inhibitor vs docetaxel efficacy in subgroups defined by patients' age. Methods: A comprehensive search of online databases was performed. The main purpose was to evaluate the difference in efficacy of immune checkpoint inhibitors between patients above age 65 and under 65, measured in terms of the difference in overall survival log(HR) reported in study participants above and under 65. A random-effects model was used to calculate the pooled overall survival HR and 95% CI in patients above and under 65. Results: A total of 19 eligible randomized controlled trials of immune checkpoint inhibitors (ipilimumab, tremelimumab, nivolumab, or pembrolizumab) that reported overall survival according to patients' age were recruited. Overall, the pooled overall survival HR was 0.75 (95% CI 0.67–0.85) (p<0.001) while the pooled progression-free survival HR was 0.72 (95% CI 0.55–0.93) (p = 0.011) in patients under age 65 treated with immune checkpoint inhibitors, compared with patients treated in control groups. In patients above age 65 treated with immune checkpoint inhibitors, the pooled overall survival HR compared with control groups was 0.80 (95% CI 0.74–0.87) (p<0.001) and the pooled progression-free survival HR was 0.81 (95% CI 0.67–0.97) (p = 0.223). The difference in efficacy between patients above and under 65 treated with immune checkpoint inhibitors was significant in overall survival. Nevertheless, there were no significant differences in progression-free survival between groups. Conclusions: Immune checkpoint inhibitors can improve overall survival for patients with advanced cancers such as non-small-cell lung cancer. However, the magnitude of benefit is age-dependent. Future research should guarantee greater inclusion of patients under age 65 in trials and focus on improving the effectiveness of immunotherapies in patients under age 65. Legal entity responsible for the study: Department of Thoracic Surgery and Oncology. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.